Land tax as the main element of the economic mechanism for efficient land management - Ualiyeva, M.A.; Syzdykova, D.I (BUKETOV BUSINESS REVIEW, 2021)
Object: To review the impact of land tax on the efficiency of agricultural development. To review the procedure for calculating land tax in Kazakhstan. To study the features of land tax collection. To consider improving the taxation of agricultural land resources. Methods: During the course of the study, we used statistical data analysis and methods of comparative analysis. Findings: This paper reviews the aspects of agricultural land plots taxation. We have analyzed a number of factors affecting the effective taxation of land resources in Kazakhstan. We have performed a comparative analysis of land taxation in the EAEU countries. We have identified key components affecting land taxation and the main parameters of their functional efficiency. Conclusions: This paper analyzes the current state of land taxation. We have developed proposals for the development of land taxation and improvement based on cadastral valuation. The results of the study allow us to conclude which of these aspects affect the effective land management.